The Influence of Compensation, Leadership, and Organizational Commitment on Employee Job Satisfaction: A Bureaucratic Perspective: at the Village and Traditional Community Empowerment Service of Papua Province - Suronoto, Muhajir; Ratang, Westim; Kambuaya, Quincy F. (Magister Manajemen Universitas Cenderawasih, 2025)
The purpose of this study was to analyze the influence of compensation, leadership, and organizational commitment, both partially and simultaneously, on employee job satisfaction at the Village and Traditional Community Empowerment Service of Papua Province. This research employed a quantitative approach with a descriptive correlational design. The study population consisted of all Civil Servants (PNS) in the service, with a sample of 111 respondents selected using the census method. Data were collected through questionnaires and analyzed using multiple linear regression with the aid of statistical software. The results showed that, partially, the variables of compensation and organizational commitment had a positive and significant influence on job satisfaction. In contrast, the leadership variable was found to have a negative and significant influence on job satisfaction. Simultaneously, compensation, leadership, and organizational commitment together had a significant influence on employee job satisfaction. These findings confirm that factors such as fair compensation, supportive leadership, and emotional attachment to the organization are crucial pillars in shaping job satisfaction. However, the different result for the leadership variable indicates complex dynamics within the bureaucratic work environment, where the leadership style implemented is not always aligned with employees' expectations for increasing satisfaction. The coefficient of determination (R^2) value of 0.885 indicates that 88.5% of the variation in job satisfaction can be explained by the three independent variables, while the remaining 11.5% is explained by other factors outside the research model.